ANALISIS SISTEM PEMASARAN BERAS LOKAL DI KAMPUNG DESAY DISTRIK PRAFI KABUPATEN MANOKWARI - Istiqomah; Ludia Theresia. Wambrauw; Yunita Palinggi (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2025)
This study aims to determine the system, marketing function, costs, margins and profits (farmer share) received by each marketing institution in Desay Village, Prafi District, Manokwari Regency. The method used in this study is a descriptive method using a case study technique, and sampling is done using the Purposive sampling method (Intentionally). Taking a sample of 30 farmers from 311 farmers, 3 collectors, 8 retailers, 1 BUMDes and 10 consumers in Desay Village. The results of the study show that the marketing system in Desay Village uses a conventional marketing system, where sellers and buyers meet directly or through intermediaries. While the marketing functions, namely purchasing sales, processing, transportation, storage, wages, standardization and risk bearing are all carried out by the BUMDes marketing institution and collectors, and retailers do not store and standardize. The costs incurred by each institution vary, depending on the needs and the amount of rice processed with an average cost of Rp / Kg., 12,721. The marketing institution that gets the most margin is BUMDes of Rp/Kg., 1,500 while the collectors and retailers get the same margin value of Rp/Kg., 1,000. The selling price in Kampung Desay is usually determined based on a mutual agreement between farmers and traders but usually not less than Rp/Kg., 12,500. The farmer share value in Kampung Desay is all above 50%, so the marketing channels in Kampung Desay can be said to be .